Pengaruh Kemudahan Akses PayLater Terhadap Perilaku Konsumtif Mahasiswa Pada Era Transaksi Digital - Syarifatul Hidayah (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the effect of easy access to PayLater on student consumer behavior in the digital transaction era. The study used a library research method with a qualitative descriptive approach. Data were obtained from various literature sources, such as scientific journals, books, academic articles, and previous research relevant to the research topic. The results of the study indicate that easy access to PayLater, characterized by a simple registration process and payment flexibility, encourages students to make transactions more easily. This condition influences the increasing tendency of impulsive purchases and consumptive behavior. In addition, digital promotions, modern lifestyles, and the influence of social media also strengthen students' interest in making purchases. This study also found that financial literacy plays a significant role in controlling PayLater use. The better students' financial understanding, the lower their tendency to engage in consumptive behavior. Therefore, improving financial literacy is necessary so that PayLater can be used more wisely and responsibly.